Our Mythical Hope The Ancient Myths as Medicine for the Hardships of Life in Children's and Young Adults' Culture - Marciniak, Katarzyna (University of Warsaw Press, 2021)
Classical Antiquity is a particularly important field in terms of "Hope studies" [...]. For centuries, the ancient tradition, and classical mythology in particular, has been a common reference point for whole hosts of creators of culture, across many parts of the world, and with the new media and globalization only increasing its impact. Thus, in our research at this stage, we have decided to study how the authors of literary and audiovisual texts for youth make use of the ancient myths to support their young protagonists (and readers or viewers) in crucial moments of their existence, on their road into adulthood, and in those dark hours when it seems that life is about to shatter and fade away. However, if Hope is summoned in time, the crisis can be overcome and the protagonist grows stronger, with a powerful uplifting message for the public. [...] Owing to this, we get a chance to remain true to our ideas, to keep faith in our dreams, and, when the decisive moment comes, to choose not hatred but love, not darkness but light. Katarzyna Marciniak, University of Warsaw, From the introductory chapter